ChemInform Abstract: Regioselective Friedel—Crafts Reactions of N‐Substituted Glyoxylamide with Indoles Catalyzed by Broensted Acid. Issue 8 (February 2016) - Zhan, Zhen; Li, Renjun; Zheng, Yang; Zhou, Yan; Hai, Li; Wu, Yong
Abstract: The title reaction gives substituted indoles [e.g. (III)] when AcOH is used as reagent, while bisindoles are obtained when 2 M HCl is used as catalyst.